A general-purpose mechanism of visual feature association in visual word identification and beyond - Vidal, Yamil; Viviani, Eva; Zoccolan, Davide; Crepaldi, Davide (Current biology, 2021)
As writing systems are a relatively novel invention (slightly over 5 kya),1 they could not have influenced the evolution of our species. Instead, reading might recycle evolutionary older mechanisms that originally supported other tasks2,3 and preceded the emergence of written language. Accordingly, it has been shown that baboons and pigeons can be trained to distinguish words from nonwords based on orthographic regularities in letter co-occurrence.4,5 This suggests that part of what is usually considered reading-specific processing could be performed by domain-general visual mechanisms. Here, we tested this hypothesis in humans: if the reading system relies on domain-general visual mechanisms, some of the effects that are often found with orthographic material should also be observable with non-orthographic visual stimuli. We performed three experiments using the same exact design but with visual stimuli that progressively departed from orthographic material. Subjects were passively familiarized with a set of composite visual items and tested in an oddball paradigm for their ability to detect novel stimuli. Participants showed robust sensitivity to the co-occurrence of features (“bigram” coding) with strings of letter-like symbols but also with made-up 3D objects and sinusoidal gratings. This suggests that the processing mechanisms involved in the visual recognition of novel words also support the recognition of other novel visual objects. These mechanisms would allow the visual system to capture statistical regularities in the visual environment.6–9 We hope that this work will inspire models of reading that, although addressing its unique aspects, place it within the broader context of vision. •Readers presented with orthographic-like stimuli are sensitive to bigram frequencies•An analogous effect emerges with images of made-up objects and visual gratings•These data suggest that the reading system might rely on general-purpose mechanisms•This calls for considering reading in the broader context of visual neuroscience Vidal et al. show that an effect usually studied in the context of reading—sensitivity to bigram frequencies—is also found when participants are presented with images of objects and circular sinusoidal gratings. This suggests that some mechanisms implied in the processing of novel words are in fact of general purpose.